1999
DOI: 10.1111/j.1600-0668.1999.t01-2-00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Household Products and Materials for Emission of Toluene Diisocyanate

Abstract: Polyurethane products were subjected to chamber testing to determine their emission rates of 2,4- and 2,6-toluene diisocyanate (TDI). The polyurethane (PU) products included carpet padding, furniture cushions, sheet foam, varnishes, and sealants, as well as a commercially-applied water sealant product for concrete that contained up to 4 percent TDI by weight. The PU products were screened in a 9-L glass chamber, under elevated temperature and chamber loading conditions, using both a time-integrated sampling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Similar results were reported in the literature for the isomers of toluylene diisocyanate (2,4-and 2,6-TDI). Kelly et al (24) measured the isocyanate emission of TDI prepolymers and found higher emission of 2,6-TDI throughout, although 2,4-TDI was the main component in the TDI resins. This was caused by the relative enrichment of 2,6-TDI during the prepolymerization process, which is described in detail by Thompson et al (25).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported in the literature for the isomers of toluylene diisocyanate (2,4-and 2,6-TDI). Kelly et al (24) measured the isocyanate emission of TDI prepolymers and found higher emission of 2,6-TDI throughout, although 2,4-TDI was the main component in the TDI resins. This was caused by the relative enrichment of 2,6-TDI during the prepolymerization process, which is described in detail by Thompson et al (25).…”
Section: Resultsmentioning
confidence: 99%
“…Emission levels from our study were lower than those observed in a study that involved a similar product-a commercial concrete sealant. (11) Kelly et al (11) reported an emission rate of 1.99 mg per gram of wet product applied for a 1-hour sample duration with essentially no emission after 1 hour. This is approximately three orders of magnitude greater than our measurements.…”
Section: Discussionmentioning
confidence: 98%
“…Formaldehyde has been a health concern, especially when released into the home environment. The 1980s had considerable studies on cured UF adhesive stability [ 7 ] identifying wood composites as a source of indoor formaldehyde emissions [ 8 ] as well as work on formaldehyde testing methods [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. There has been a long-term decline in the emissions from particleboard, especially as countries look at tightening the allowed emissions [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%